Artificial Intelligence in Early Childhood Education: Challenges and Opportunities from An Islamic Religious Education Perspective - Epy Pujiaty; Fahrisya Rahayul Hadi (Jurnal Ilmiah Teunuleh, 2026)
This study discusses the use of artificial intelligence in early childhood education from the perspective of Islamic religious education. The background of this research emerged because AI technology began to be used in children's learning, but it was not fully aligned with Islamic moral values and teachings. This study aims to explain how AI is used in early childhood learning, identify opportunities that can be utilized, and identify challenges that arise in its use. The method used is qualitative with a literature study approach, which involves collecting and reading various journals, books, and scientific sources related to research topics, and then analyzing them by grouping, comparing, and compiling findings so that they are easy to understand. The results of the study show that AI can facilitate learning to be more interesting, fast, and in accordance with children's abilities through media such as games, videos, chatbots, and smart learning systems. AI makes it easier for teachers to prepare materials and understand children's development. However, challenges such as the risk of misunderstanding religious teachings, reliance on technology, reduced social interaction, and ethical and data security issues exist. In Islamic religious education, AI cannot replace the role of teachers because teachers guide morals and set direct examples. Therefore, AI should be used as a tool that remains under the guidance of teachers and parents so that learning runs well without leaving religious values.